Analisa Perbandingan Metode SAW, WP dan TOPSIS Dalam Sistem Pendukung Keputusan Pada Kasus Pemilihan Manajer - Ilham Ramdani; Syahrul Ramadan; Risky Tuah Sinaga; Wahyu Diansyah; Robby Jordan (CV. Multi Kreasi Media, 2023)
In making a decision, it is necessary to have the right consideration so that you don't regret making a decision.If a wrong step in making a decision will certainly be fatal for the person who made the decision.Therefore we need a system that can analyze a decision.Decision support systems are one of the sciences of information systems that are intended as a tool for decision making.Decision support systems are designed to offer decision makers different options for completing tasks.Decision support systems incorporate computational capabilities into interactive services to users by processing or manipulating data using certain structured models or rules to produce various decisions in decision-making situations.There are several methods analyzed in decision making systems such as simple additive weighting (SAW), product weight (WP), Technique for Order Preference by Similarity to Ideal Solution (TOPSIS).